Implementation of Policy for Arranging Street Vendors in Singkawang City - Yeni Lestari; Samugyo Ibnu Redjo; Neneng Yani Yuningsih (Journal of Law, Politic and Humanities, 2025)
This study aims to describe and analyze the implementation of the Policy for the Arrangement of Street Vendors on Jalan Merdeka to Lapangan Tarakan, Singkawang City. The analysis was conducted using the policy implementation theory from Merilee S. Grindle which includes content and context variables. This study uses a descriptive qualitative method with an inductive approach. Data collection techniques include observation, interviews, and documentation studies. The results of the study indicate that the involvement of the government, street vendors, and the community in the planning and implementation process of the policy is very important to achieve the desired goals. The Street Vendor Arrangement Policy has accommodated the interests of all target groups, namely street vendors affected by relocation and the community. This program provides types of academic, social, and environmental benefits that are felt directly, fairly, and evenly. This policy has also succeeded in encouraging positive changes in environmental and social aspects, thus creating a public space that can be enjoyed by all levels of society. However, in terms of resources, both budget, human resources and infrastructure are still inadequate so they need to be improved. The implementation of this policy involves various actors with different powers, interests, and strategies, but in general shows high commitment and support. The characteristics of the implementing agency, such as a flexible organizational structure, responsive organizational culture, and strong leadership, also support the success of implementation. In addition, street vendors' compliance with regulations and government responsiveness to community aspirations are key factors in the success of policy implementation. However, in terms of resources, both budget, human resources and infrastructure, they are still inadequate and need to be improved.